Preventive effect of swim bladder hydrolysates on cyclophosphamide‐induced ovarian injury in mice. Issue 2 (1st December 2021) - Ge, Enhui; Zha, Rui; Gao, Qing; Guo, Lirong; Wang, Binglong; Lin, Qiqi; Zhang, Guifeng; Xie, Weiquan; Yin, Hui; Liu, Tao
Abstract: Aims: This study aimed to prepare swim bladder hydrolysate (SBH) with M n  < 4000 Da, and investigate its effects on cyclophosphamide (CTX)‐mediated ovarian injury in mice. Methods: Hydrolysates were prepared by heating extraction, enzymatic hydrolysis and ultrafiltration. M n and distribution of SBH were analyzed via gel filtration chromatography and matrix‐assisted laser desorption/ionization time‐of‐flight mass spectrometry. Changes in the mouse oestrus cycle were determined by cytological examination. The number of follicles was examined using histopathology. Enzyme‐linked immunosorbent assays (ELISAs) were used to determine the serum sex hormone levels. Results: The M n of SBH, prepared by heating extraction, enzymatic hydrolysis, ultrafiltration, and from different batches, was below 4000 Da, and the preparation process was stable. Compared with the control group, the low‐, middle‐, and high‐dose SBH treatment groups showed different trends in oestrus duration, serum sex hormone levels, and the number of primordial and secondary follicles. The oestrus cycle duration of the high‐dose SBH group was longer than that of the model group. The serum luteinizing hormone, follicle‐stimulating hormone, and anti‐Müllerian hormone levels in the middle‐dose group were the closest to those of control group. The number of primordial and secondary follicles in the medium‐dose group was significantly higher than that in the model group and closest to those of control group. Conclusion: After heating extraction, trypsin/Flavourzyme hydrolysis and ultrafiltration, a hydrolysate with M n below 4000 Da could be prepared. We found that a moderate (400 mg/kg) SBH dose resulted in the greatest effect on ovarian injury remission in mice.